In vivo Raman spectroscopy reveals biochemical changes in the human cervix with pregnancy establishment - Emily E. Spurlin; Katy Belcher; Folaoluwashewa Shofu; Jennifer A. E. Esteves; Patricia T. Jimenez; Christine M. O’Brien (npj Women's Health)
Abstract The cervix is a vital component of pregnancy: it provides a protective barrier during the antepartum period and undergoes drastic remodeling to facilitate parturition. There is a wealth of research that studies cervical remodeling during late pregnancy and labor, but few studies investigate the cervix during the earliest weeks of gestation. This study focuses on biochemical changes that occur between the time just prior to conception and 6–8 weeks gestation by enrolling patients undergoing intrauterine insemination. In vivo Raman spectroscopy was utilized as a nondestructive tool to identify early biochemical changes within the cervix. The study found the early cervical remodeling included increased vascularity, decreased structural proteins, and decreased trivalent collagen cross-linking. This is the first study demonstrating the feasibility of using in vivo Raman spectroscopy to measure biochemical changes upon the transition to early pregnancy and indicates that cervical remodeling begins in the earliest stages of pregnancy.